2013
DOI: 10.1136/bjophthalmol-2012-302327
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ocular abnormalities in adults with Down syndrome in Hong Kong

Abstract: Background/aims This was a cross-sectional survey to find the prevalence of visual impairment and eye diseases among adults with Down syndrome (DS) in Hong Kong. Methods 91 DS patients over the age of 30 were recruited through the Hong Kong Down Syndrome Association. Each patient was provided with a complete ophthalmological assessment including best corrected visual acuity, refraction, slit lamp and fundus examination. Results In our sample, 56.6% had normal vision to mild vision impairment, 33.7% and 7.2% ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 27 publications
3
29
0
1
Order By: Relevance
“…The study did not find a correlation between the magnitude of refractive error and the severity of intellectual disability. Similarly, Fong and colleagues found a range of spherical equivalent refractive errors from ‐23.25 to +3.00 D in patients with DS, with 59 per cent of DS participants being myopic with an average spherical refractive error of ‐5.75 ± 4.6 D. Significant astigmatism (defined as 1.00 D or more) was found in 72 per cent of patients, with the average value being 2.06 ± 1.1 DC; however, Fong and colleagues’ study was carried out on Chinese patients with DS, which does not represent the global prevalence. The prevalence of myopia in patients with intellectual disabilities varied between 18 and 33 per cent among other populations .…”
Section: The Complexity Of Ocular Manifestationsmentioning
confidence: 97%
See 1 more Smart Citation
“…The study did not find a correlation between the magnitude of refractive error and the severity of intellectual disability. Similarly, Fong and colleagues found a range of spherical equivalent refractive errors from ‐23.25 to +3.00 D in patients with DS, with 59 per cent of DS participants being myopic with an average spherical refractive error of ‐5.75 ± 4.6 D. Significant astigmatism (defined as 1.00 D or more) was found in 72 per cent of patients, with the average value being 2.06 ± 1.1 DC; however, Fong and colleagues’ study was carried out on Chinese patients with DS, which does not represent the global prevalence. The prevalence of myopia in patients with intellectual disabilities varied between 18 and 33 per cent among other populations .…”
Section: The Complexity Of Ocular Manifestationsmentioning
confidence: 97%
“…The prevalence of significant refractive error found in patients with intellectual disabilities and the rate of spectacle prescribing is not in a linear relationship. Studies have shown lower spectacle prescription rates for people who were institutionalised (24 per cent) compared to those who lived at home (45 per cent) and yet more significant refractive errors were found in those living in institutions . McCulloch and colleagues demonstrated that more spectacles were prescribed for patients with mild intellectual disabilities and prescribing rates dropped in groups with more severe intellectual disabilities.…”
Section: Management and The Continuity Of Carementioning
confidence: 99%
“…The incidence of Down's syndrome in Hong Kong is 1.28 per 1000 live births,19 which is slightly higher than the 1.00 per 1000 live births reported in the USA 20. The incidence of age-related cataract in patients with Down's syndrome has been shown to be as high as 35–50% 8 21 22. The occurrence of early cataract has been attributed to multiple factors such as susceptibility to oxidative stress23 and accumulation of amyloid precursor protein and amyloid-β peptides24 25 in the lens.…”
Section: Discussionmentioning
confidence: 93%
“…Of these, refractive errors and cataract should be corrected at the earliest in order to avoid preventable ocular morbidity related to these disorders. A recent study from Hong Kong revealed the incidence of refractive errors and cataracts in adult patients with Down's syndrome to be 86.3% and 72.2%, respectively 8. The authors suggested that uncorrected refractive errors and cataracts are the main visually debilitating ophthalmological abnormalities in this group of patients 8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation